Overload robust IGBT design for SSCB application - Supono, I.; Urresti, J.; Castellazzi, Alberto; Flores, D. (Elsevier, 2014)
This paper presents an optimised power semiconductor architecture based on the CIGBT approach to be used in solid-state circuit breaker (SSCB) applications where the conduction losses have to be as low as possible without compromising the forward voltage blocking capability. Indeed, a high overcurrent turn-off and short-circuit withstand capabilities have to be ensured. Starting from a standard NPT-IGBT design for switching applications, the results show that the proposed device, which is optimised by the application of the individual clustered concept, offers a reduction in conduction losses of 13%, without compromise on voltage blocking capability. An original design solution is implemented to further ensure short-circuit and overload turn-off capabilities at maximum ambient temperature and twice the nominal rated current.